Musicology, Discourse, and the Performer’s Body: Understanding Music from the Inside - Morrison, Krystal (Université d'Ottawa / University of Ottawa, 2018)
Current research in music scholarship appears to be trending towards the “embodied” yet from the vantage point of the performer this progression seems to be lacking a key component of such an embodied discourse: their voice. In this thesis I argue that the oversight of the performing body and its importance to the field of musicology is a result of conceptual dualities that attempt to conceal the body in its role within thought, culture, and meaning. Illustrating this oversight with the gaps in the current academic discourse, I show how many in the field either consider the body only in a metaphorical sense, or see the performer as an object of study. An examination of the contributions of three performer-scholars to this field demonstrates ways in which the gap can be filled, and lack addressed. Their approaches are then combined in an embodied analysis of Messiaen’s “Abîme des Oiseaux” from Quatour pour la Fin du Temps which reveals the potentialities of depth and breadth that can be considered when the performer’s body is permitted to be a site from which a musical analysis might originate. This thesis concludes that the performing body must be reintroduced into musicological discourse with a new understanding of its value, and that this can best be accomplished by addressing the “embodied” within the academic music curriculum, alongside traditional tonal and formal analyses.
Keywords: Performance Studies; Embodiment